Hypertrophic cardiomyopathy: therapies and treatments - Naidu, Srihari (Henry Stewart Talks, 2020)
What is Hypertrophic Cardiomyopathy?, Natural history of the disease, Current surgical and non-surgical treatments, Novel treatments